Positive discourse analysis of the Indonesian government spokesperson's discursive strategies during the Covid-19 pandemic - Sultan,; Muhammad Rapi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The Covid-19 pandemic that is sweeping across the globe has caused increased anxiety. Studies in linguistics have found a variety of language expressions that convey people's anxiety and fear. However, there are only a few researchers that studied the use of language used in communication by the government, to enhance the citizens' morale and help them recover from psychological distress from the Covid-19 pandemic. This study focused on investigating the discursive strategies used by the Indonesian government spokesperson at daily press conferences during the Covid-19 pandemic. This study employed the Positive Discourse Analysis (PDA) framework. A total of 28 recorded press conference sessions that lasted between 25-45 minutes were analyzed through the identification, interpretation, and explanation stages. Identification was carried out through careful reading of the transcription of the government spokesperson’s speech to find out the discursive strategy used by the spokesperson. The interpretation was done by grouping similar quotes with the same themes, based on the context of the discourse. The explanation was done by explaining, in a macro way, the situational aspects and social contexts that provide the background for the texts’ production and relating them to the pandemic. The results of the study showed that the spokesperson made use of nomination, predication, argumentation, perspectivization and intensification, and mitigation strategies to deliver information to the public. The entire discursive strategies are used to improve the public’s optimism and build solidarity of the citizens as a moral force to face the pandemic. Suggestions for future research about analysis of pandemic discourse employed by the government include corpus analysis, power representation and framing.